TINJAUAN YURIDIS TERHADAP TINDAK PIDANAPENGANIAYAAN DALAM PERTANDINGAN SEPAKBOLA DI INDONESIA DIKAITKAN DENGAN ASAS LEX SPORTIVA - Salsabila Afnita; Erdianto Erdianto (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
The offense of maltreatment in a legal framework is considered a crime, namely an act that is subject to sanctions by law. The criminal act of maltreatment is an ordinary offense, which means that reporting is not a condition for filing a lawsuit. In addition, the Federation International de Football Association (FIFA) as the International Federation of football which controls and has sovereignty over football, organizing professional football competitions also requires legal guarantees and security guarantees from the state as outlined in the licensing mechanism listed in article 1 of the FIFA Diciplinary Code Preliminary Title.Football matches in Indonesia are often chaos. One example of a fight between players in a professional football match occurred in a match between clubs from Central Java Persis Solo against clubs from East Java Gresik United. The case had a long tail and caused a stir for football players in Indonesia because it entered the court and became a beating case that was dragged into national law. In the development of football in Indonesia there is the Indonesian Football Association (PSSI), as the association that houses and represents FIFA. After the football parent organization was ratified, the PSSI as the main force for football organizations in the country formed regulations that functioned to regulate the matches organized by PSSI, known as the League Manual Rules. The League Manual Rules were made as an effort to maintain sportsmanship in competing and also to protect players from harsh and rough elements.This research will be prepared using the type of normative juridical research, namely research that is focused on examining the application of the rules or norms in positive law regarding legal principles, the legal principles used in this study are Lex Sportiva's legal principles. The approach used in this research is to use a normative approach, namely literature law research. The results of the research conducted by the author are, first to find out how the lex sportiva is applied to criminal acts of persecution in Indonesian football. And the results of research to see and justify reasons and excuses for forgiveness for athletes who injure playmates.Keywords: Law enforcement - denial of coinsn – Indonesia Football